GOOGLE EARTH VIRTUAL JOURNEY TO IMPROVE WRITING SKILLS OF HIGH SCHOOL STUDENTS IN MALANG - Astrid Wangsagirindra Pudjastawa (Jurusan Sastra Indonesia, 2022)
They are responding to the current situation of the COVID-19 pandemic, which has affected the world of education in Indonesia. This study aims to develop writing skills using virtual field trips. Virtual field trips based on google earth are used as field trip learning innovations visualized digitally based on internet technology to support the implementation of field studies without leaving the classroom. This research uses Action Research research. From each cycle that was applied, students showed their active participation in producing descriptive paragraph text and showed their willingness to communicate and discuss. These results reflect students' acceptance of the applied learning method because they feel that the applied method helps improve their writing skills